A permanência do idoso no mundo do trabalho como motorista de aplicativo em Curitiba - Lanzarin, Jane (2022)
The growth of the Brazilian elderly population has been observed in several surveys conducted by the Brazilian Institute of Geography and Statistics (IBGE). They have also pointed out that the elderly, even when already retired, continue to represent a significant portion of the national workforce, whether in formal or informal jobs, often requiring adaptations of various kinds. Among these adaptations, those related to technological knowledge required for the use of devices inherent to the performance of their functions stand out, knowledge to which many of them have not had access. In this context, the main objectives of this study are to investigate the relationships that the elderly establish with technology in the exercise of their work and the justifications that make them remain productively active. Thus, the research focuses on the elderly, their performance in the world of work, their perception of the meaning of work, and their relationship with technology. The research, carried out with elderly people whose current professional occupation is to be na app driver in the city of Curitiba, Paraná, aimed to analyze aspects related to their life trajectories, their previous professional occupations, and the way they learn and relate to the technology required in this occupation. Based on a qualitative nature, the literature review addressed theoretical issues related to work, technology, the elderly’s work performance, and legislation related to the elderly. Data were obtained through interviews and questionnaires applied virtually to eight participants selected by the snowball research technique. The interviewees were approached on issues related to their family and professional history, technological learning and difficulties for work practice, as well as their perception of work and happiness. The reports showed financial issues as the main reason for them to remain active in the world of work, mainly because only a few of the interviewees had financial reserves. Regarding the technological resources necessary for the activity practiced, no major difficulties were pointed out for their learning and use. The practicality of exercising the profession and the flexibility of schedules were considered attractive by the interviewees. However, most of them responded that they did not feel happy or fulfilled, admitting to being in the activity because they did not have another opportunity and because age is na impediment to professional repositioning. The study also pointed out the need to deepen discussions on the scenario of elderly employability and better use of their productive potential.